Phytodiversity in Relation to Some Environmental Factors Of Some Wetland Habitats (Bangladesh Journal of Botany, 2021)
The present research work was carried out on phytodiversity in relation to some environmental factors of three ponds namely, Pond-1, Pond-2 and Pond-3 of Zanjira upazila at Shariatpur district, Bangladesh where a total of 13 parameters were measured for one year. Monthly average different parameters of three ponds varied : air temperature from 23.5-36.50˚  C, water temperature 21-30.50 ˚  C,pH 7.10-8.50, TDS 55-227 mg/l, EC 103-463 μS/cm, DO 2.90-19.94 mg/l, alkalinity 0.73-5.40 meq/l, SRP 7.11-229.84 μg/l, SRS0.84-13.34 mg/l, NO3-N0.02-0.96 mg/l, chla1. 18-31.97 μg/l, phaeopigment 0.26-5.46 μg/l and phytoplankton density 6.50-119.50×106 ind/l. The total number of 122 species of phytoplankton were recorded in the studied ponds. Phytoplankton density showed positive correlation with air temperature, water temperature, pH, TDS, EC, alkalinity and SRP for Pond-1. Phytoplankton density showed positive correlation with pH, TDS, EC, DO and alkalinity for Pond-2. On the other hand phytoplankton density of Pond-3 showed positive correlation with air temperature, water temperature, TDS, EC, alkalinity, SRP, SRS, NO3-N and chlorophyll-a. During the period of present investigation some aquatic plants were found to grow in those shallow margins of the studied three ponds. Results indicated that Pond-1 is in a position undergoing eutrophic status, Pond-2 and Pond-3 are in the oligotrophic status. If the anthropogenic disturbances are continued in these ponds, it is likely that in near future these ponds would turn to eutrophic.Bangladesh J. Bot. 50(4): 1087-1094, 2021 (December)